2018
DOI: 10.1111/jcmm.13442
|View full text |Cite
|
Sign up to set email alerts
|

GP73 promotes invasion and metastasis of bladder cancer by regulating the epithelial–mesenchymal transition through the TGF‐β1/Smad2 signalling pathway

Abstract: This study investigated the effects of Golgi membrane protein 73 (GP73) on the epithelial–mesenchymal transition (EMT) and on bladder cancer cell invasion and metastasis through the TGF‐β1/Smad2 signalling pathway. Paired bladder cancer and adjacent tissue samples (102) and normal bladder tissue samples (106) were obtained. Bladder cancer cell lines (T24, 5637, RT4, 253J and J82) were selected and assigned to blank, negative control (NC), TGF‐β, thrombospondin‐1 (TSP‐1), TGF‐β1+ TSP‐1, GP73‐siRNA‐1, GP73‐siRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…TGF-β signalling is undoubtedly a central player in cancer progression due to its dual functioning [42]. Not to mention, TGF-β acts as a lymph node metastatic biomarker [60] and is involved in the invasion and metastasis of BLCA [61,62]. Furthermore, TGF-β reprograms the tumour microenvironment to attenuate anti-tumour immunity in metastatic bladder cancer [63].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β signalling is undoubtedly a central player in cancer progression due to its dual functioning [42]. Not to mention, TGF-β acts as a lymph node metastatic biomarker [60] and is involved in the invasion and metastasis of BLCA [61,62]. Furthermore, TGF-β reprograms the tumour microenvironment to attenuate anti-tumour immunity in metastatic bladder cancer [63].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, EIF5A2 stimulates TGF-β1 expression via STAT3 to induce EMT and stimulate migration and invasion [208] while cancer-associated fibroblasts (CAFs) secrete Kindlin-2, which induces EMT in a TGF-β-dependent manner [209]. The TGF-β1/SMAD2 pathway is also utilized by Golgi membrane protein 73 (GP73) to induce EMT and promote invasion and metastasis of bladder cancer [210]. TGF-β1 mediates signaling initiated by collagens.…”
Section: Bladder Cancermentioning
confidence: 99%
“…[8][9][10][11] Concordantly, many functional studies reported that GP73 could promote proliferation and migration of tumor cells. 12,13 However, more studies from other laboratories and our own demonstrated the common presence of increased serum GP73 in patients of liver cirrhosis with different etiologies. 14,15 As mentioned above, the cell proliferation promoting role of GP73 in HCC cells has been confirmed by a number of researches.…”
Section: Introductionmentioning
confidence: 75%
“…In recent years, numerous studies have reported the significant increase of serum GP73 level in patients with hepatocellular carcinoma (HCC) and proposed it as a marker for HCC diagnosis 8–11 . Concordantly, many functional studies reported that GP73 could promote proliferation and migration of tumor cells 12,13 . However, more studies from other laboratories and our own demonstrated the common presence of increased serum GP73 in patients of liver cirrhosis with different etiologies 14,15 …”
Section: Introductionmentioning
confidence: 76%